THE RIGHT TO EDUCATION OR THE RIGHT TO HEALTH - GOOD GOVERNANCE CAN CHOOSE BETWEEN THEM? - Oana ŞARAMET (CKS 2021 Nicolae Titulescu University, Bucharest, 2021)
Any human society will seek to educate its next generations, passing on to them its most precious values, thus it will ensure that this supreme values will be forwarded in the future. But anyway it will put at least the same price on the health of its members. Moreover, in any contemporary society in which democratic values, such as freedom and dignity of the human being, but also fundamental rights and freedoms are declared and guaranteed by the fundamental, constitutional law, the education and health of its members must be central elements of any government. Good governance must be individualcentered, it must aim every member of society concerned. But when a society struggles to pass by a deep crisis, there is a risk of conserving its resources to use them only for what it needs to get out of that crisis. In our opinion, there is even more risk of doing so when that crisis is a public health crisis, such as the one from nowadays. In such situations, we ask ourselves if at least the values mentioned above are protected, but also if and which of them should be guaranteed to the human being, perhaps more than ever in such periods. Indeed, any government will have to appreciate and decide, fully assuming the decision taken, how it will still be able to ensure good governance in such unfavourable conditions, ensuring and guaranteeing not only the right to health but also the right to education, among other fundamental rights and freedoms. In this paper, we will search for answers to the above, as we will try to find out if there is a legitimate and moral possibility to give priority to one of the two rights, if we could use the principle of proportionality to answer this dilemma, but also if good governance, in special situations, can be realised by prioritizing one of these rights. In this paper, we will search for answers to the above, we will try to find out if there is a legitimate and moral possibility to give priority to one of the two rights, but also if we could use the principle of proportionality to answer this dilemma, and if good governance, in special situations, can be realised by prioritizing one of these rights.
Keywords: fundamental right; health; education; proportionality; good governance.